Synthesis and docking studies of some novel quinoline derivatives bearing a sulfonamide moiety as possible anticancer agents - Ghorab, Mostafa M.; Ragab, Fatma A.; Hamed, Mostafa M. (Arzneimittelforschung, 2010)
Sulfonamides posses many types of biological activities and have recently been reported to show substantial antitumor activity in vitro and/or in vivo. There is a variety of mechanisms for the anticancer activity of the sulfonamide compounds and the most prominent of these is the inhibition of carbonic anhydrase isozymes. The present work reports the synthesis of some novel quinoline and pyrimido [4,5-b] quinoline derivatives bearing a sulfonamide moiety. The structures of these compounds were confirmed by elemental analysis, IR, 1H-NMR and mass spectral data. All the newly synthesized compounds were evaluated for their in vitro anticancer activity against breast cancer cell line (MCF7). Most of the screened compounds showed interesting cytotoxic activities compared with the used reference drugs. In addition, docking of the synthesized compounds into carbonic anhydrase isozyme II (CA II) active site was performed in order to predict the affinity and the orientation of these compounds at the isozyme active site.
Keywords: Anticancer agents Carbonic anhydrase Quinolines Sulfonamide